1996
DOI: 10.1097/00006123-199605000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Dysesthetic Pain in Patients with Syringomyelia

Abstract: Dysesthethic pain is a common complaint of patients with syringomyelia, traumatic paraplegia, and various myelopathic conditions. Because cavitary lesions of the spinal cord can be defined with good resolution by magnetic resonance imaging, syringomyelia provides a potential model for examining anatomic correlates of central pain. In this study, a syndrome of segmental dysesthesias, characterized by burning pain, hyperesthesia, and a variable incidence of trophic changes, was described by 51 of 137 patients (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 46 publications
1
33
0
1
Order By: Relevance
“…Below-level pain after SCI may, for example, involve damage to the dorsal columns, because pain as-sociated with syringomyelia is reported to be more prevalent when a central cavity expands to include dorsal pathways [74] . Similarly, animal models of dysesthesia/ pain have shown that interruption of the dorsal or dorsolateral columns increases the incidence of overgrooming/ autotomy after peripheral nerve injury, and allodynia/hyperalgesia is observed in response to stimulation caudal and ipsilateral to dorsolateral column lesions in monkeys.…”
Section: Animal Models Of Below-level Painmentioning
confidence: 99%
“…Below-level pain after SCI may, for example, involve damage to the dorsal columns, because pain as-sociated with syringomyelia is reported to be more prevalent when a central cavity expands to include dorsal pathways [74] . Similarly, animal models of dysesthesia/ pain have shown that interruption of the dorsal or dorsolateral columns increases the incidence of overgrooming/ autotomy after peripheral nerve injury, and allodynia/hyperalgesia is observed in response to stimulation caudal and ipsilateral to dorsolateral column lesions in monkeys.…”
Section: Animal Models Of Below-level Painmentioning
confidence: 99%
“…69 This pain always has a delayed onset, perhaps even may be years after the SCI. The development of a syrinx is characterized by new neurological de®cits at a higher level than the original injury.…”
Section: Syringomyeliamentioning
confidence: 99%
“…The persistence of dysesthetic pain (especially in group B) was characteristic for patients with collapse of their syrinxes [35]. Patients of both groups had similar bony and CSF space abnormalities at the CVJ and PF (Table) [16,43,45].…”
Section: Discussionmentioning
confidence: 88%